2014
DOI: 10.1167/iovs.14-14188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravitreal Triamcinolone Acetonide or Bevacizumab on Choroidal Thickness in Eyes With Diabetic Macular Edema

Abstract: Citation: Sonoda S, Sakamoto T, Yamashita T, et al. Effect of intravitreal triamcinolone acetonide or bevacizumab on choroidal thickness in eyes with diabetic macular edema. Invest Ophthalmol Vis Sci. 2014;55:3979-3985. PURPOSE.We evaluated the effect of intravitreal triamcinolone acetonide (IVTA) or intravitreal bevacizumab (IVB) on subfoveal choroidal thickness (SFCT) in eyes with diabetic macular edema (DME). METHODS.In this prospective, randomized, interventional comparative study, 51 DME eyes of 51 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 31 publications
2
44
1
Order By: Relevance
“…Other recent studies reported similar results showing that despite reduction of the DMO after intravitreal triamcinolone, significant improvement of vision was not achieved. 16 Because of the chronic nature of DMO in our study, eyes may have already sustained chronic and irreversible microstructural damage to photoreceptors, and this may have caused a limitation on the improvement of visual acuity. Perhaps, it may be more effective to perform IVD injection at an early stage before imposing burdens of multiple anti-VEGF injections on patients and it may lead to concurrent improvement of visual acuity along with morphological improvement of DMO before eyes sustain chronic damage to the photoreceptors in the macula.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Other recent studies reported similar results showing that despite reduction of the DMO after intravitreal triamcinolone, significant improvement of vision was not achieved. 16 Because of the chronic nature of DMO in our study, eyes may have already sustained chronic and irreversible microstructural damage to photoreceptors, and this may have caused a limitation on the improvement of visual acuity. Perhaps, it may be more effective to perform IVD injection at an early stage before imposing burdens of multiple anti-VEGF injections on patients and it may lead to concurrent improvement of visual acuity along with morphological improvement of DMO before eyes sustain chronic damage to the photoreceptors in the macula.…”
Section: Discussionmentioning
confidence: 88%
“…21,22 Regarding the effect of specific treatment on subfoveal CT, a recent study showed that intravitreal triamcinolone injection caused significant reduction of subfoveal CT, whereas such reduction was not observed in those receiving intravitreal anti-VEGF injections. 16 However, another recent study by Yiu et al 23 showed significant decrease of subfoveal CT after multiple anti-VEGF injections. In their study, however, the decrease of subfoveal CT after anti-VEGF injection was not associated with either the number of injections, changes in BCVA, or CFT.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A randomized, prospective trial found that IVTA was associated with a sustained reduction of choroidal thickness in patients with DME; the choroidal thickness remained unchanged after IVB [69]. Color Doppler imaging of ocular hemodynamics after IVTA and IVB found that the end diastolic volume decreases in the ophthalmic artery and posterior ciliary arteries after IVTA while peak systolic velocity and end diastolic volume decrease significantly in the ophthalmic artery after IVB [70].…”
Section: Triamcinolone Acetonidementioning
confidence: 99%